The imPAct of Trimetazidine on MicrOcirculation after Stenting for stable coronary artery disease (PATMOS study) - Ilic, Ivan; Timcic, Stefan; Milosevic, Maja; Boskovic, Srdjan; Odanovic, Natalija; Furtula, Matija; Dobric, Milan; Aleksandric, Srdjan; Otasevic, Petar (Frontiers in Cardiovascular Medicine, 2023)
Background Myocardial ischemia is caused by epicardial coronary artery stenosis or atherosclerotic disease affecting microcirculation. Trimetazidine (TMZ), promotes glucose oxidation which optimizes cellular energy processes in ischemic conditions. Small studies demonstrated protective effects of TMZ in terms of reducing myocardial injury after percutaneous coronary intervention (PCI), its effect on microcirculation using contemporary investigative methods has not been studied. The aim of the study was to examine effects of trimetazidine, given before elective PCI, on microcirculation using invasively measured index of microcirculatory resistance (IMR). Methods This was prospective, single blinded, randomized study performed in a single university hospital. It included consecutive patients with an indication for PCI of a single, de novo, native coronary artery lesion. Patients were randomly assigned to receive either TMZ plus standard therapy (TMZ group) or just standard therapy. Coronary physiology indices fractional flow reserve (FFR), coronary flow reserve (CFR) and index of microcirculatory resistance (IMR) were measured before and after PCI using coronary pressure wire. Results We randomized 71 patients with similar clinical characteristics and risk profile, previous medications and coronary angiograms. Patients had similar values of Pd/Pa, FFR and CFR prior to PCI procedure. After PCI, FFR values were higher in TMZ group, while IMR values were lower in this group respectively (FFR TMZ + 0.89±0.05 vs TMZ – 0.85±0.06, p=0.007; CFR TMZ+2.1±0.8 vs TMZ- 2.3±1.3, p=0.469; IMR TMZ+ 18±9 vs TMZ- 24±12, p=0.028). In two-way repeated measures ANOVA PCI was associated with change in FFR values (TMZ p=0.050; PCI p<0.001; p for interaction 0.577) and TMZ with change in IMR values (TMZ p=0.034, PCI p=0.129, p for interaction 0.344). Conclusion Adding trimetazidine on top of medical treatment prior to elective PCI reduces microvascular dysfunction by lowering postprocedural IMR values when compared to standard therapy alone.